1998
DOI: 10.1073/pnas.95.8.4556
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of human copper,zinc-superoxide dismutase (SOD1) prevents postischemic injury

Abstract: Superoxide and superoxide-derived oxidants have been hypothesized to be important mediators of postischemic injury. Whereas copper,zinc-superoxide dismutase, SOD1, efficiently dismutates superoxide, there has been controversy regarding whether increasing intracellular SOD1 expression would protect against or potentiate cellular injury. To determine whether increased SOD1 protects the heart from ischemia and reperfusion, studies were performed in a newly developed transgenic mouse model in which direct measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
3
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(141 citation statements)
references
References 40 publications
5
130
3
3
Order By: Relevance
“…Others, however, studied the protection of CuZn-sod against hypoxia-reoxygenation damage, which is also free radical mediated. 14,18,32,33 In the present experiment, significant levels of CuZnsod were produced in NeRCaMs at the third day of infection with AdCuZn-sod compared to noninfected cells. However, the occurrence of cellular cytotoxicity limited the MOI of AdCuZn-sod to 25 PFU/cell.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Others, however, studied the protection of CuZn-sod against hypoxia-reoxygenation damage, which is also free radical mediated. 14,18,32,33 In the present experiment, significant levels of CuZnsod were produced in NeRCaMs at the third day of infection with AdCuZn-sod compared to noninfected cells. However, the occurrence of cellular cytotoxicity limited the MOI of AdCuZn-sod to 25 PFU/cell.…”
Section: Discussionsupporting
confidence: 46%
“…Previous experiments, showed that only high level of Mn-sod protected against LDH and CK increase in the serum of transgenic mice. 16 Also complete protection was only obtained with a 10-fold increase in CuZn-sod in transgenic mice 32 while less than five-fold increase in sod activity did not fully protect against free radicals produced by doxorubicin 17 or hypoxia/reoxygenation. 14 MonoHER is a semisynthetic flavonoid.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by the findings that knockout mice deficient in copper-zinc superoxide dismutase (CuZnSOD) or cellular glutathione peroxidase (Gpx1) are more sensitive to cardiac I/R injury, and transgenic mice overexpressing either of these enzymes exhibit a resistant phenotype [41][42][43][44][45]. Analogously, overexpression of Grx1 in H9c2 cardiomyocyte cells in vitro protects them from H 2 O 2 -induced apoptosis [29], however an in vivo effect of genetic manipulation of Grx1 has not been reported.…”
Section: Mice Deficient In Grx1 Do Not Display Greater Myocardial Injmentioning
confidence: 99%
“…Overexpression of human CuZnSOD in mice, resulting in a 10-fold higher level in both myocytes and endothelial cells, was able to quench a burst of superoxide (electron probe resonance [EPR] detection) and reduce functional damage following 30 min global ischemia [105]. These results suggest that superoxide is an important factor in protecting against postischemic injury.…”
Section: Antioxidant Enzymes and Proteins Involved In Transition Metamentioning
confidence: 97%